Floodplain modeling due to dam break using CCHE2D_FLOOD - Omar, Nurul Atiqah (2013)
The prediction of floodplains caused by dam break is very important to discuss for future planning and decision making concerning to dam safety, controlling downstream developments, contingency evacuation planning and real time flood forecasting. The objectives of this study are (1) to determine the propagation of flood in the study area, in terms of water depth and velocity magnitude, and (2) to identify the potential area of high risk of flooding. The comparison of results using one point source input flood discharge (total discharge) and flood hydrograph have been carried out. The floodplain simulation in this study using software is called as CCHE2D_FLOOD model. The study area is at Durian Tunggal Dam, located in Melaka. The dam has been classified as a significant hazard dam with a catchment area of 41.4 km2, impounded area of 5.8 km2 and a storage volume of 32.6 Mm3. A flood hydrograph due to dam break, observed by Rahimah (2009) is used as a model parameters input to simulate the propagation of flood in the surrounding areas of Durian Tunggal river. The results of water depth, velocity distribution, and time required to flooding are the parameters that needed to be analysed